2015
DOI: 10.1039/c4nr05637j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-modified electrodes for enhancing the performance of microbial fuel cells

Abstract: Graphene is an emerging material with superior physical and chemical properties, which can benefit the development of microbial fuel cells (MFC) in several aspects. Graphene-based anodes can enhance MFC performance with increased electron transfer efficiency, higher specific surface area and more active microbe-electrode-electrolyte interaction. For cathodic processes, oxygen reduction reaction is effectively catalyzed by graphene-based materials because of a favorable pathway and an increase in active sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(80 citation statements)
references
References 86 publications
0
76
0
Order By: Relevance
“…Currently, graphene (GE) and graphene-base materials have drawn much attention in electrode and supercapacitor applications due to their impressive mechanical and electrochemical properties [12][13][14]. Importantly, graphene oxide (GO), as the most familiar graphene-base material, can be made in large quantities with less cost than GE or carbon nanotubes (CNTs) via chemical method [15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, graphene (GE) and graphene-base materials have drawn much attention in electrode and supercapacitor applications due to their impressive mechanical and electrochemical properties [12][13][14]. Importantly, graphene oxide (GO), as the most familiar graphene-base material, can be made in large quantities with less cost than GE or carbon nanotubes (CNTs) via chemical method [15].…”
Section: Introductionmentioning
confidence: 99%
“…4d), which was around 1.2 times higher than that achieved in Pt/C-MFC under identical conditions (19.3 A m −3 ) [14,52]. However, the conductivity of regular NG was measured to be 35 S m −1 , which was still 10 S m −1 lower than Pt/C [4,50]. Therefore, it is of crucial importance to maximize the conductivity of graphene cathodes in practical applications.…”
Section: Metal Free Catalysts Cathode Catalystsmentioning
confidence: 76%
“…Besides this, a desirable anode material should be biocompat-ible so that bacteria introduced into the system will form a biofilm on the anode, while a favorable cathode material should have a highly electrocatalytic activity toward oxidants (e.g., oxygen) reduction reaction. However, high cost of cathode catalysts and low charge transfer efficiency of electrodes restrict the development of MFC technology [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since this pioneering study, activated carbon has been used frequently as a cathode catalyst in different types of MFCs 27, 28, 29, 30, 31. It should be noted that other carbonaceous materials such as carbon nanotubes,32 activated carbon fibers,33 modified carbon black,34 and graphene35, 36, 37, 38 were also studied as cathode catalysts in MFCs. On the other hand, systematic research into carbonderived cathodes revealed intrinsic low ORR activities, high overpotentials, and low power generation.…”
Section: Introductionmentioning
confidence: 99%